Carbon nanofiber based electrochemical biosensors: A review - Huang, J.; Liu, Yang; You, T. (R S C Publications, 2010)
Carbon nanofibers (CNFs), a novel carbon nanomaterial, have the similar conductivity and stability to carbon nanotubes (CNTs). The main distinguishing characteristic of CNFs from CNTs is the stacking of graphene sheets of varying shapes, producing more edge sites on the outer wall of CNFs than CNTs, which can facilitate the electron transfer of electroactive analytes. The unique chemical and physical properties make CNFs exceptional candidates for electrode materials and promising candidates as immobilization substrates. This review is an attempt to give an overview on electrochemical biosensors based on CNFs and their various applications. We discussed the application of CNFs as electrode material in electroanalysis, as well as their functionalization and surface immobilization. Vertically aligned carbon nanofibers (VACNFs) as substrates for the immobilization of biological molecules have also been discussed.